STRATEGI PENGEMBANGAN PENDIDIKAN ISLAM DI PERGURUAN TINGGI AGAMA ISLAM (PTAI) - Saiful Saiful (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2014)
PTAI existence in this globalization era demanded an active role in developing the Islamic studies. Likewise develop the social sciences, humanities independently as part of Islamic studies. PTAI as Islamic educational institutions must develop Islamic education development strategy that refers to the Islamic epistemology. Epistemological occupies a strategic position in the development of Islamic education in PTAI, because he talked about how to get the right knowledge. The strategy of development of Islamic education in PTAI, among others, are (1) Reconstruction of Islamic Studies at PTAI. (2) Developing the Islamic sciences. (3) The use of science to aid the study of Islam. (4) Increased research faculty. (5) Improved quality standards PTAI, (6) Modernization PTAI. (7) Strengthening of Islamic education in PTAI epistemology. The effort to develop Islamic education in PTAI namely a) PTAI align themselves with the demands of modern, b) PTAI need to recreate a new paradigm of Islamic education, c) PTAI need to reorient education vision and mission, goals, management, organizational structure, materials and teaching methods, and culture community, d) PTAI should be orientation on improving the quality of faculty and students, e) development of Islamic education is directed through research, f) paradigm PTAI forward directed at cultural paradigm rather than natural, g) PTAI able to translate normative religion into science theoretical.